2012
DOI: 10.1080/07448481.2011.584334
|View full text |Cite
|
Sign up to set email alerts
|

Individual, Interpersonal, and Institutional Level Factors Associated With the Mental Health of College Students

Abstract: Simultaneously addressing the individual and institutional level influences on mental health offers the most promising help for students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
158
0
17

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(184 citation statements)
references
References 40 publications
(36 reference statements)
9
158
0
17
Order By: Relevance
“…Building upon these, and other promising examples, there is an opportunity to explore how course design and delivery can enhance student well-being and learning. Within a higher education context, several authors have emphasized the importance of exploring the impacts of institutional factors, such as learning environments, on student well-being (Byrd & Mckinney, 2012;Dooris & Doherty, 2010;Okanagan Charter, 2015), however we did not find any articles that explicitly aimed to explore students' own definitions of and experiences with well-being in higher education learning environments. Given ongoing debates about how well-being should be defined and enacted within various contexts (Dodge, Daly, Huyton, & Sanders, 2012;Soutter, O'Steen, & Gilmore, 2012), it is relevant and important to ground an understanding of well-being in learning environments in students' own experiences and interpretations through a grounded theory approach (Strauss & Corbin, 1994).…”
Section: Literature Reviewmentioning
confidence: 77%
“…Building upon these, and other promising examples, there is an opportunity to explore how course design and delivery can enhance student well-being and learning. Within a higher education context, several authors have emphasized the importance of exploring the impacts of institutional factors, such as learning environments, on student well-being (Byrd & Mckinney, 2012;Dooris & Doherty, 2010;Okanagan Charter, 2015), however we did not find any articles that explicitly aimed to explore students' own definitions of and experiences with well-being in higher education learning environments. Given ongoing debates about how well-being should be defined and enacted within various contexts (Dodge, Daly, Huyton, & Sanders, 2012;Soutter, O'Steen, & Gilmore, 2012), it is relevant and important to ground an understanding of well-being in learning environments in students' own experiences and interpretations through a grounded theory approach (Strauss & Corbin, 1994).…”
Section: Literature Reviewmentioning
confidence: 77%
“…Moreover, they need to avoid any high stress which is becoming increasingly worrying, as it has been found that the number of psychological problems and their severity are on the rise among student population [10][11][12]. Hence, problems such as fi nancial restrain [13], time constraints, which limit the time left to complete their assignment and research paper due to working, classes and family [8] affect students' psychological well-being.…”
Section: Introductionmentioning
confidence: 99%
“…The years of higher education are often perceived as stressful, and this experience is related to factors at the individual and organizational levels (Byrd & McKinney, 2012;Vollestad, Nielsen, & Nielsen, 2012). Prolonged stress reactions are detrimental to one's health and can interfere with learning and lead to burnout (McEwen & Gianaros, 2011;Rudman & Gustavsson, 2012).…”
Section: Introductionmentioning
confidence: 99%